Age-related changes of the root apex of the tooth an adult (LLC "Endo Press", 2020)
Studied 62 teeth removed for medical reasons in 54 adults (32 men and 22 women) of different ages to determine age-related changes in the root tips of teeth.Were used methods of odontoscope, x-ray examination, and prepared and studied thin sections of tooth roots. It is established that with age, in the absence of resorption of the apex and gipertireoze in the apex of the tooth root, in adults there is a reduction of the diameter of the root canal in the apical third of the root, due to the formation of secondary dentine, as well as a slight thickening of the cement in the region of apical hole. Thus, increases with age the distance between apical constriction, apical foramen and the radiographic apex of the tooth root. People young and middle age obliteration of root canal teeth are studied according to x-rays does not occur. In elderly and senile obliteration of the root canals of the teeth in the area of the tops are marked at 75% and 79%, respectively, but in thin sections of the roots, which according to x-ray examination is determined by the obliteration of the cavity of the tooth root, the channels typically have a lumen, that is, they are passable for endodontic instruments.